IMPLEMENTASI FLEET MANAGEMENT SYSTEM BERBASIS MOBILE LAYANAN RENTAL BUS PARIWSATA MENGGUNAKAN METODE R&D (STUDI KASUS : PT.NUSAWISATA TRANS) - Ramadhan, Agung Wahyu; Ananda, Jecky Tri; Firdaus, Muhammad; Alda, Muhammad (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
Fleet management is an important component in bus rental business operations. Common problems include limited monitoring of bus availability, poorly organized vehicle usage records, and manual management of driver data and travel schedules. These conditions result in low operational efficiency and poor service quality for customers. This study aims to implement a mobile-based Fleet Management System in bus rental businesses to support integrated fleet management. The method used is Research and Development (R&D), which includes the stages of needs analysis, system design, application development, testing, and evaluation. The results of the study show that the developed system is able to assist managers in monitoring fleet status, managing bus usage schedules, and organizing driver and trip data more effectively. This system is expected to improve operational efficiency and support the decision-making process in bus rental businesses.